2017
DOI: 10.1186/s40529-017-0211-9
|View full text |Cite
|
Sign up to set email alerts
|

Nostoc calcicola extract improved the antioxidative response of soybean to cowpea aphid

Abstract: BackgroundSoybean (Glycine max (L.) Merr. cv. “Nam Dan”) is one of the most valuable crops in agricultural production in Nghe An province (Vietnam). Our previous study revealed that extract of the cyanobacterium strain Nostoc calcicola HN9 expressed positive effect on growth and development, and raised soybean productivity (Tran et al. in Proceeding of Vietnam national conference of research on biology, Da Nang, 2016). We hypothesized that N. calcicola HN9 would improve the defense responses of G. max cv. “Nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The effect of aphid presence on the induction of antioxidant response in host plants has been demonstrated in many published studies [51,[59][60][61]. Additionally, Kerchev et al [59] showed that the perturbations in the leaf antioxidant system are intrinsic to the potato leaf response to peach-potato aphid (Myzus persicae Sulzer).…”
Section: Discussionmentioning
confidence: 97%
“…The effect of aphid presence on the induction of antioxidant response in host plants has been demonstrated in many published studies [51,[59][60][61]. Additionally, Kerchev et al [59] showed that the perturbations in the leaf antioxidant system are intrinsic to the potato leaf response to peach-potato aphid (Myzus persicae Sulzer).…”
Section: Discussionmentioning
confidence: 97%
“…However, most studies have measured ROS at a small number of timepoints between 2 and 96 h after infestation ( Tables 1 , 2 ). Of the time series conducted within this range, the majority suggest a transient ROS response that peaks on or before 24 h and then declines, often returning to baseline levels 3–4 days after treatment ( Moloi and Van Der Westhuizen, 2006 ; Moloi and van der Westhuizen, 2014 ; Ren et al, 2014 ; Sytykiewicz, 2015 ; Mai et al, 2016 , 2017 ; Łukasik et al, 2017 ; Shao et al, 2019 ; Woźniak et al, 2019 ). Certain time series studies, however, did not detect significant increases in ROS until well after 24 h ( Kerchev et al, 2012 ; Yao et al, 2020 ), or observed ROS levels that peaked after 24 h and/or continued to increase steadily in the days following infestation ( Borowiak-Sobkowiak et al, 2016 ; Sun et al, 2016 ; Zhang et al, 2019 ).…”
Section: Characteristics Of the Reactive Oxygen Species Response To A...mentioning
confidence: 99%
“…Therefore, certain incompatible interactions also appear to involve long-term ROS accumulation. In addition, the limited number of studies that have utilized more than one probe for ROS detection indicate that H 2 O 2 and O 2 – can in some cases differ from one another in their onset and persistence ( Mai et al, 2013 , 2017 ; Sun et al, 2016 ; Czerniewicz et al, 2017 ), and that the timing of the oxidative response to aphids also varies among subcellular compartments ( Xu et al, 2021 ).…”
Section: Characteristics Of the Reactive Oxygen Species Response To A...mentioning
confidence: 99%
See 1 more Smart Citation